An Enhanced Bandwidth Optimization in Un-reliable Network using Efficient Bandwidth Utilization based Scheduling Algorithm - Sivashanmugam N; Jyoti Venkateshwaran (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Nowadays, bandwidth utilization is a very challenging task for Subscriber Stations (SS) to predict a large amount of data. The existing techniques allow the SS to maintain the occupied bandwidth via risk of failure which does not satisfy the quality of services (QoS) needs.  Another challenge is the resource handling with QoS. In Web technology life, there is only few research focused on tackling the resource handling issues with different techniques. Current methods do not consider the data interchange during route switching.  To offer the best solution of above problems, An Efficient Bandwidth Utilization based Scheduling (EBS) Algorithm is designed to maintain proper bandwidth utilization in a real-time application. The EBS algorithm predicts the amount of bandwidth which should be requested according to backlogged traffic data. It’s also considering the data rate divergence between a packet received and transmissions in a queue to improve the bandwidth. The main objective of proposed design is to permits other complementary station (CS) and SSs to bring out the unutilized bandwidth by the availability of SS transmission. The unutilized bandwidth is not possible to get regularly. The proposed method is more flexible to apply in real time and research-oriented applications. The methods enhance the bandwidth utilization during maintenance of the same QoS guaranteed network services. A proposed method avoids the current bandwidth reservation collapse at the time of the same QoS guaranteed services.  The techniques permit SSs to find out the portion of un-utilized bandwidth accurately. Based on Experimental evaluations, proposed algorithm reduces 21.26 PLR (Packet Loses Ratio), 3.25 AD (Average Delay), and improves 8.65 BU (Bandwidth Utilization) and 51.2% (Throughput) compared than existing methods.